Bibliometric Analysis of the Effectiveness of Waste Management and Recycling Programs in the Textile Industry - Loso Judijanto; Yamtana Yamtana; Rival Pahrijal (West Science Interdisciplinary Studies, 2024)
This bibliometric study provides a comprehensive analysis of the evolution and current trends in waste management and recycling within the textile industry, spanning from 1970 to 2024. Utilizing VOSviewer for keyword co-occurrence analysis, the research highlights a significant shift from basic waste management to advanced, sustainable practices integrated into textile production. The study reveals an increased focus on technologies such as wastewater treatment and recycling innovations, reflecting the industry's response to global sustainability demands. The findings illustrate the interdisciplinary nature of textile waste management research and underscore the importance of technological advancements in promoting environmental sustainability. However, the study also identifies ongoing challenges, including regional disparities in waste management effectiveness and the need for global standards. The study emphasizes the necessity for future research to address these challenges, proposing a continued focus on innovative, adaptable recycling technologies and comprehensive waste management strategies that can be implemented globally.